Switchable matched ring resonator in SPDT discrete switch design for WiMAX and LTE in 3.5 GHz band - Shairi, N.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper proposes the application of switchable matched ring resonators in Single Pole Double Throw (SPDT) discrete switch design. The proposed design is demonstrated for Time Division Duplex (TDD) switching of wireless data communication systems such as WiMAX and LTE in 3.5 GHz band. The switchable matched ring resonators provide an absorptive feature as well as high isolation in the SPDT discrete switch. Therefore, results in simulation and measurement show more than 10 dB of return loss at absorptive ports and more than 30 dB of isolation from 3.4 to 3.6 GHz. Copyright 2014 IEICE.